2015
DOI: 10.1016/j.jams.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Wound Healing Properties of Rubus ellipticus Smith.

Abstract: The present investigation has been undertaken to study the antioxidant, antitumor, and wound healing properties of Rubus ellipticus. The R. ellipticus leaves were extracted using organic solvents in Soxhlet and were subjected to in vitro antioxidant assays. R. ellipticus leaf methanol (RELM) extract, which showed higher in vitro antioxidant activity, was taken for the evaluation of in vivo antioxidant, antitumor, and wound healing properties. Acute oral and dermal toxicity studies showed the safety of RELM up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 23 publications
2
22
0
2
Order By: Relevance
“…These phytoconstituents express reductive activity on free radicals and may limit the appearance of mutations or even participate in DNA repair [24]. There are a few reports concerning the antitumour activity of other Rubus leaves extracts, but no data are available supporting the extracts from dewberry leaves [15, 16, 22, 25, 26]. Previous studies on in vitro models suggest that berry from Rubus species may influence colorectal cancer cell survival in concert terms proliferation and apoptosis [17].…”
Section: Resultsmentioning
confidence: 99%
“…These phytoconstituents express reductive activity on free radicals and may limit the appearance of mutations or even participate in DNA repair [24]. There are a few reports concerning the antitumour activity of other Rubus leaves extracts, but no data are available supporting the extracts from dewberry leaves [15, 16, 22, 25, 26]. Previous studies on in vitro models suggest that berry from Rubus species may influence colorectal cancer cell survival in concert terms proliferation and apoptosis [17].…”
Section: Resultsmentioning
confidence: 99%
“…The methanol extract of Rubus ellipticus leaves showed antioxidant activity and antitumor and wound-healing properties in incision, excision, and Staphylococcus aureus-induced-infected wound models and mice with Ehrlich ascites carcinoma [119].…”
Section: Other Plant Species Used In Wound Healingmentioning
confidence: 99%
“…The results showed nearest value of indomethacin. Abdel-Aziz et al [61] designed a group of cyclic imides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and evaluated its selective COX-2 inhibition. The molecular docking study showed that the CH 3 O substituents of 5b were inserted firmly to COX-2, where the O-atoms of such group underwent a H-bonding interaction with HIS 90 (2.43, 2.83Å), ARG 513 (2.89Å), and TYR 355 (3.34Å).…”
Section: Molecular Docking Of Isolated Compounds Against Brcamentioning
confidence: 99%
“…The literature showed that the berries (Rubus sp.) of Rosaceae family have been reported for their strong antioxidant and pharmacological properties [5][6][7][8][9] and various bioactive free radical scavenging compounds were isolated [10][11][12][13][14]. Berry fruits are characterized by a high content and wide diversity of bioactive compounds such as phenolic compounds, organic acids, tannins, anthocyanins, and flavonoids [15].…”
Section: Introductionmentioning
confidence: 99%